The pathophysiologic aspects and clinical implications of electrocardiographic parameters of ventricular conduction delay in repaired tetralogy of Fallot - Udink ten Cate, Floris E.A.; Sreeram, Narayanswami; Brockmeier, Konrad (Journal of electrocardiology, 2014)
The 12-lead surface electrocardiogram is a valuable and feasible clinical tool in the management of patients following tetralogy of Fallot (TOF) repair. The importance of QRS duration in TOF patients has long been acknowledged. A prolonged QRS complex has been associated with increased risk for subsequent life-threatening ventricular arrhythmia and sudden cardiac death. Our current ability to risk-stratify TOF patients for malignant arrhythmogenic events primarily on the basis of QRS duration is rather limited. Nevertheless, increasing evidence suggests that QRS morphology and duration may be useful as surrogate markers of infundibular and regional right ventricular myocardial disease. The aim of this review is to provide a critical appraisal of the clinical implications of established and new electrocardiographic markers of ventricular conduction delay in TOF patients following surgical correction with a particular focus on QRS duration, lengthening, and fragmentation. In addition, the pathophysiological background of these parameters is addressed.